Nexus between postpartum depression and exclusive breastfeeding practices among lactating mothers in Assosa Town, West Ethiopia - Abdurehim, Abdulfeta; Melaku, Yabsra; Hassen, Habtamu; Mosa, Hassen; Jemal, Musa; Abawari, Mohammed Jemal; Kemal, Abdurezak; Mohammed, Tofik; Biru, Bayise; Alemu, Emana; Ali, Anwar Seid; Mohammed, Bekri; et al. (Frontiers in Nutrition, 2024)
Background Across the globe, breastfeeding stands out as a highly effective strategy for reducing infant and child morbidity and mortality. Concurrently, postpartum depression (PPD) emerges as a notable public health issue, adversely affecting both exclusive breastfeeding (EBF) practices for infants and the fulfillment of parenting roles. Despite the lack of substantial evidence in Ethiopia and the specific study areas, indicating the association between PPD and EBF practices, this study endeavors to fill this gap. The primary objective is to examine the correlation between PPD and EBF practices, along with exploring other pertinent factors, in Assosa Town, West Ethiopia. Methods A community-based cross-sectional study was carried out from 7 March to 5 April 2019. The study involved the recruitment of 462 participants through a systematic random sampling method. Data collection was facilitated by conducting a structured and pre-tested questionnaire. To screen for PPD, we used the Edinburgh Postnatal Depression Scale (EPDS) tool. This tool, EPDS, was used solely as a screening tool and not for diagnostic purposes. The collected data were entered into Epi-Data version 3.1 and subsequently exported to SPSS version 24 for comprehensive statistical analysis. Bivariate and multivariate logistic regression analyses were performed to assess the association between independent variables and dependent variables. Odds ratios, along with their 95% confidence intervals (CIs), were calculated to ascertain the presence and strength of any associations. Statistical significance was acknowledged at a p-value of <0.05. Results The overall prevalence of EBF practices was found to be 58.2% (95% CI: 51.4–65.7), while the prevalence of PPD was 18.7% (95% CI: 15.94–26.7). Among mothers without PPD, the prevalence of EBF practices was notably higher at 62.4% (95% CI: 55.9–65.2%) compared to mothers experiencing PPD, where the prevalence was 31.3% (95% CI: 24.7–32.5%). Mothers who experienced PPD exhibited 51% reduced odds of practicing EBF compared to their counterparts (AOR = 0.49. 95% CI: 0.25–0.8). Furthermore, factors such as having a higher family monthly income (AOR = 8.7, 95% CI: 4.2–17.2), being multiparous (AOR = 5.8, 95% CI 4.9–10.8), attending antenatal care (ANC) visits (AOR = 4.9, 95% CI: 3.4–14.1), opting for vaginal delivery (AOR = 9.8, 95% CI: 5.6–17.4), and receiving husband’s support (AOR = 5.3, 95% CI: 4.6–12.7) demonstrated a statistically significant positive association with EBF practices. Conclusion In this study, a substantial number of mothers demonstrated suboptimal EBF practices during the first 6 months of their infants’ lives. Consequently, the findings underscore a clear association between PPD and EBF. Thus, it is imperative to intensify efforts in the early detection and treatment of PPD, enhance household income, advocate for ANC, and encourage active husband involvement to bolster EBF practices.